GOOD CORPORATE GOVERNANCE IN GREEN FINANCING FOR RENEWABLE ENERGY ISLAMIC BUSINESS ETHICS PERSPECTIVE - Haryati; Heri Junaidi; Abdul Mughits; Nik Abdul Rahim Nik Abdul Ghani (istinbath, 2026)
Good corporate governance (GCG) is increasingly important in ensuring that green financing for renewable energy is not reduced to a formal environmental label, but is managed through transparent, accountable, responsible, independent, and fair decision-making. This study examines how renewable-energy financing can be strengthened through the integration of GCG and Islamic business ethics. Using normative-conceptual library research, the article analyses regulations, green-financing instruments, energy-management literature, and Islamic ethical principles. The study proposes a TARIF-Amanah Green Financing Governance Model, which links each GCG principle to Islamic ethical values and to concrete governance mechanisms in project screening, use of proceeds control, impact reporting, sharia supervision, and stakeholder protection. The findings show that Islamic business ethics deepens conventional GCG by transforming governance from procedural compliance into moral accountability before God, society, and the environment. In this framework, green sukuk and sustainable finance policies become stronger when they apply credible eligibility criteria, measurable environmental impacts, and safeguards against greenwashing. The article concludes that renewable-energy financing requires not only capital mobilization, but also ethical governance that protects public welfare and ecological balance